El régimen simple de tributación con la reforma tributaria consagrada en la ley 2277 de 2022 (2023)
This research article focuses on the analysis of the Simple Tax Regime, an innovative approach aimed at simplifying the tax collection process for SMEs. What the R.S.T seeks is to facilitate the payment of taxes, avoiding long payment processes, generating savings when paying your obligations in a unified manner, providing rates which are more suited to the level of income and payments to which you apply. can access voluntarily.